The Effect of Telemedicine Consultation on Outcomes in Patients with Intracerebral Hemorrhage - A. M. Alasheyev; A. A. Smolkin; E. V. Prazdnichkova; A. A. Belkin (Неотложная медицинская помощь, 2020)
RELEVANCE. Telemedicine solves the problem of the availability of highly qualified personnel at the decision-making stage in the management of patients with intracerebral hemorrhage. AIM OF STuDY We set out to evaluate the effect of teleconsultation on outcomes in patients with intracerebral hemorrhage 30 days after the event.MATERIAL AND METHODS. A prospective, open, nonrandomized clinical trial in two parallel groups. The first group included adult patients up to 80 years of age with a hemorrhagic stroke from 4 to 36 points according to NIHSS due to unilateral supratentorial intracerebral hematoma of non-aneurysmal genesis, who were examined by a neurosurgeon and resuscitator of the Regional Vascular Center in a ward. The second group included similar patients, but they received telemedicine consultation of the above specialists. The primary endpoint of the study was mortality 30 days after the onset of the stroke. The hypothesis of non-superiority was tested where the 95% confidence interval (CI) for the difference in mortality between the groups should not go over 15 percentage points.RESULTS. A total of 140 patients (70 in each group) with intracerebral hematomas were studied. Mortality in the bedside group was 14.3% (CI 7.1%; 24.7%), and in the remote group it was 25.7% (16.0%; 37.6%), p=0.091. However, there was no evidence of superiority, since the difference between the groups in mortality was 11.4 with CI from –0.07 to 24.5 percentage points, which was beyond the predefined limit.CONCLUSIONS. At the current level of development of medicine and information technology, telemedicine cannot fully replace the traditional (bedside) consultation of an expert level of neurosurgeon and neuroresuscitator in patients with intracerebral hematomas.Authors declare lack of the conflicts of interests.